Mechanical Properties Of Concrete With Different Types Of Glass Waste As Cement Replacement Material - Bakar, Amir Syazwan Abu (Universiti Sains Malaysia, 2022)
Concrete is a structural material that comprised as a mixture of aggregates that is bonded together by cement and water. It is a very necessary and useful substances for construction work that is easy to create into varies shapes and sizes. Concrete can be designed in various strength to overcome the load applied on the structure of the building or other structural designs but the production of cement in concrete can caused harm toward environment. To reduce the environmental effect of cement production, glass is being reused to replace the cement in the concrete mixture. In this study, the effect of cement replacement in concrete with glass waste was evaluated in term of slump testing, compressive strength and density evaluation. The aim of this study is to determine the mechanical properties of concrete by using glass waste in powder form as cement replacement material and to determine the effect of using different type of glass waste sorted by colour on compressive strength. The procedure of preparing the mixture were carried out by preparing 5 types of samples with different type of glass and percentage replacement of glass powder with cement. Slump test were conducted for each of the sample variation to determine the rate of workability when replacing the cement in concrete. Curing process for all the samples were performed for 7 days and 28 days for strength determination and also dry density for hardened concrete. Data collected for compressive strength were evaluated based on 7 days and 28 days of strength to ensure the suitability and effect of using glass waste powder for cement replacement. Several test had been evaluated for the concrete sample which were slump test, compressive strength test and density determination. For compressive strength test, the strength for controlled sample with no cement replacement was higher compared to 10% and 15% of glass powder replacement. Density of concrete sample also decrease when replaced with glass powder for both 7 days and 28 days of curing.